1999
DOI: 10.1107/s0907444999009877
|View full text |Cite
|
Sign up to set email alerts
|

Cryocrystallography of a Kunitz-type serine protease inhibitor: the 90 K structure of winged bean chymotrypsin inhibitor (WCI) at 2.13 Å resolution

Abstract: The crystal structure of a Kunitz-type double-headed alpha--chymotrypsin inhibitor from winged bean seeds has been refined at 2.13 A resolution using data collected from cryo-cooled (90 K) crystals which belong to the hexagonal space group P6(1)22 with unit-cell parameters a = b = 60.84, c = 207.91 A. The volume of the unit cell is reduced by 5.3% on cooling. The refinement converged to an R value of 20.0% (R(free) = 25.8%) for 11100 unique reflections and the model shows good stereochemistry, with r.m.s. devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Recent X -ray crystallography structure of winged bean, Psophocarpus tetragonolobus Kunitz-type double headed alpha-chymotrypsin shows 12 anti-parallel beta strands joined in a form of beta trefoil with two reactive site regions (Asn 38-Leu 43 and Gln 63-Phe 68) at the external loops (Ravichandaran et al 1999;Mukhopadhyay, 2000). Structural analysis of the Indian finger millet ( Eleusine coracana) bifunctional inhibitor of alpha-amylase/trypsin with 122 amino acids has shown five disulphide bridges and a trypsin binding loop (Gourinath et al 2000).…”
Section: Serine Proteinase Inhibitorsmentioning
confidence: 99%
“…Recent X -ray crystallography structure of winged bean, Psophocarpus tetragonolobus Kunitz-type double headed alpha-chymotrypsin shows 12 anti-parallel beta strands joined in a form of beta trefoil with two reactive site regions (Asn 38-Leu 43 and Gln 63-Phe 68) at the external loops (Ravichandaran et al 1999;Mukhopadhyay, 2000). Structural analysis of the Indian finger millet ( Eleusine coracana) bifunctional inhibitor of alpha-amylase/trypsin with 122 amino acids has shown five disulphide bridges and a trypsin binding loop (Gourinath et al 2000).…”
Section: Serine Proteinase Inhibitorsmentioning
confidence: 99%
“…The trypsin-specific inhibitor cospin from C. cinerea utilizes the ␤2-␤3 loop of the crown region, which is a different loop from those involved in other ␤-trefoil-fold protease inhibitors. Macrocypin 4 from Macrolepiota procera utilizes the crown region loop ␤5-␤6 for inhibition of trypsin and asparaginyl endopeptidase (41), whereas the root region loop ␤4-␤5 is functional in the inhibition of chymotrypsin by the winged bean chymotrypsin inhibitor (45), of trypsin by Kunitz-type STI (37), and of porcine pancreatic elastase and human neutrophil elastase by Bauhinia bauhinioides cruzipain inhibitor (46). This indicates that the ␤-trefoil fold can serve as a fundamental scaffold to which different inhibitory loops can be attached at different positions.…”
Section: Discussionmentioning
confidence: 99%
“…Although these loops originate from different subdomains they have very weak sequence constraints -providing a platform for its functional diversity [17]. Although extensive structural and inhibitory studies have been reported for the Kunitz (STI) family [18][19][20][21][22][23], very little is known about their core packing compared to the FGF and interleukin family. As several crystal structures having β-trefoil fold are available in Protein Data Bank (PDB) we felt it necessary to revisit their hydrophobic core with special emphasis on Kunitz (STI) family.…”
Section: Introductionmentioning
confidence: 98%